The Impact of Aging on Brain Pituitary Adenylate Cyclase Activating Polypeptide, Pathology and Cognition in Mice and Rhesus Macaques - Han, Pengcheng; Nielsen, Megan; Song, Melissa; Yin, Junxiang; Permenter, Michele R.; Vogt, Julie A.; Engle, James R.; Dugger, Brittany N.; Beach, Thomas G.; Barnes, Carol A.; Shi, Jiong (Frontiers in Aging Neuroscience, 2017)
Pituitary adenylate cyclase activating polypeptide (PACAP) is associated with Alzheimer’s disease (AD), but its age-related effects are unknown. We chose the rhesus macaque due to its closeness to human anatomy and physiology. We examined four variables: aging, cognitive performance, amyloid plaques and PACAP. Delayed nonmatching-to-sample recognition memory scores declined with age and correlated with PACAP levels in the striatum, parietal and temporal lobes. Because amyloid plaques were the only AD pathology in the old rhesus macaque, we further studied human amyloid precursor protein (hAPP) transgenic mice. Aging was associated with decreased performance in the Morris water maze. In wild type C57BL/6 mice, the performance was decreased at age 24-26 month whereas in hAPP transgenic mice, it was decreased as early as 9-12 month. Neuritic plaques in adult hAPP mice clustered in hippocampus and adjacent cortical regions, but did not propagate further into the frontal cortex. Cerebral PACAP protein levels were reduced in hAPP mice compared to age-matched wild type mice, but the genetic predisposition dominated cognitive decline. Taken together, these data suggest an association among PACAP levels, aging, cognitive function and amyloid load in nonhuman primates, with both similarities and differences from human AD brains. Our results suggest caution in choosing animal models and in extrapolating data to human AD studies.